Exploiting Reservoir Computing for Optical Secure Communication. Issue 1 (1st April 2022) - Tang, Qianfeng; Xie, Yiyuan; Jiang, Xiao; Liu, Bocheng; Chai, Junxiong; Ye, Yichen; Song, Tingting; Feng, Manying
Abstract: A reservoir computing (RC) based on vertical cavity surface emitting laser (VCSEL) subjected to optical feedback is adopted to realize chaos synchronization in optical chaotic communication. Combined with the application of chaos masking (CMS) technology in chaotic secure communication, chaotic signal generated by distribution feedback (DFB) laser after optical feedback and optical injection, that is used as chaotic carrier of hiding original information, and act as target signal of the RC. Then masked information is used for RC training and transmission. Next, utilizing the weights and error offsets trained out by RC at transmitter, carrier can be reconstructed by RC at receiver. Finally, message is acquired by subtracting the reconstructed carrier from received masked signal. Taking image data transmission in 10 km fiber as an example, the chaos synchronization between the carrier signal and the constructed carrier signal is 0.9935, Q-factor is 10 and bit error rate (BER) is 5×10 -28 with simulation.